Plantão psicológico com casais e famílias em situação de crise: aprimorar o atendimento, conhecer as expectativas dos encaminhadores, o perfil dos atendidos e as experiências do pós-atendimento - Fernandes, Álvaro Rebouças (2021)
This thesis has the objective of improving the psychological duty with couples and families, developed in the University of Fortaleza. In this research, a mixed method, which was organized into three studies, was used. In the first study, the motives were identified, the needs and the expectations of the forwarders, through an on-line eleven-question Google Forms questionnaire, shared via WhatsApp to the participants. According to the results: the majority of the forwarders (16) were from the healthcare area, particularly psychologists (13), while the most sought-after services were: the sessions at the psychological clinic (22) and the Service of Applied Psychology (SPA) was the psychological duty with couples and families (20). The socio-economic conditions of the majority of the couples and families indicated to the service were from the lower and middle classes. The motives for the referrals were: psychiatric situations, troubles and conflicts with their children or teenagers, conflicts and marital difficulties, extended family interaction and relationship problems and grief over the death of relatives. The forwarders informed the need to increase the number of vacancies, expand the access to the existing services, as well as the creation of the missing services at the location. In the second study, a characterization of the families and their demands was done, based on the documental analyses of the attended cases between the period of 2016 and 2019. The results showed that the majority of the couples and families who sought sessions were composed by four people (24), with predominance of nuclear families (27). Predominantly women (86), between the ages of 20 and 59 years (79) and graduated from high school (58). Most of the people had informal occupations/ jobs (54), who went through normative crises (40) and had communication issues as their main complain (55). The third study was a qualitative research, done with the utilization of the case study method, in which we tried to understand the perception about the session process, the adherence to the forwarders and the resolution of the brought issues. The participants for this research were eight couples and/or families who sought and finished their session in the year of 2019. All of the interviewed informed that there were improvements, rapprochement between the members, union, learning, awareness about their difficulties, knowledge, and mutual understandings. The couple and all of the families commented that there was total or partial resolution of the brought issues, although the results of the FACES III do not indicate changes in the functional sense. For the couple and the interviewed families, the sessions had multiple impacts that helped them comprehend each other’s opinions, to ponder about actions that could be changed, get emotionally closer, get united and respect each other, talk more and search for possible solutions. They revealed that now the couple and the families are a lot better, trying to continue their relationship, trying to deal with the perceived problems properly, aggregate values, maturing, understanding each other, in a more united and closer way. However, some also reported that it has been problematic, difficult, and troubled living through rather hard moments of stress and lack of peace. In regard to the importance of the psychological duty as a service, they approved its existence and the importance of its work. They affirmed that the service was relevant and impacted a lot their lives, was essential to solve conflicts, valid, enriching, and necessary. However, stressed the need of it being expanded and more divulged